HUMAN RIGHTS AND THE ORIGIN OF MYTHS OF POST-APARTHEID SOUTH AFRICAN FOREIGN POLICY (The Strategic Review for Southern Africa, 2020)
The foreign policy narrative of South Africa is strongly grounded in human rights issues, beginning with the transition from a racial segregation regime to a democracy. The worldwide notoriety of the apartheid South Africa case was one factor that overestimated the expectations of the role the country would play in the world after apartheid. Global circumstances also fostered this perception, due to the optimistic scenario of the post-Cold War world order. The release of Nelson Mandela and the collapse of apartheid became the perfect illustration of the victory of liberal ideas, democracy, and human rights. More than 20 years after the victory of Mandela and the first South African democratic elections, the criticism to the country's foreign policy on human rights is eminently informed by those origin myths, and it generates a variety of analytical distortions. The weight of expectations, coupled with the historical background that led the African National Congress (ANC) to power in South Africa, underestimated the traditional tensions of the relationship between sovereignty and human rights. Post-apartheid South Africa presented an iconic image of a new bastion for the defence of human rights in the post-Cold War world. The legacy of the miraculous transition in South Africa, though, seems to have a deeper influence on the role of the country as a mediator in African crises rather than in a liberal-oriented human rights approach. This is more evident in cases where the African agenda clashes with liberal conceptions of human rights, especially due to the politicisation of the international human rights regime.
Keywords: foreign policy of South Africa; human rights; racial segregation regime; democracy; apartheid; post-Cold War; Nelson Mandela; post-apartheid; origin myths; African National Congress (ANC); sovereignty; international human rights